2016
DOI: 10.3340/jkns.2016.59.3.250
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Temperature-Sensitive, Anti-Adhesive Agent on the Reduction of Adhesion in a Rabbit Laminectomy Model

Abstract: ObjectiveA common cause of failure in laminectomy surgery is when epidural, peridural, or perineural adhesion occurs postoperatively. The purpose of this study is to examine the efficacy of a temperature-sensitive, anti-adhesive agent (TSAA agent), Guardix-SG®, as a mechanical barrier for the prevention or reduction of peridural scar adhesion in a rabbit laminectomy model.MethodsTwenty-six mature rabbits were used for this study. Each rabbit underwent two separate laminectomies at lumbar vertebrae L3 and L6, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Among various anti-adhesive agents, we have used a poloxamer 407/188-based thermosensitive gel (Mediclore®, CGbio Co., Ltd. Seongnam-si, Korea) [10]. The agent is a complex consisting of poloxamer 407/188, chitosan, and gelatin.…”
Section: Methodsmentioning
confidence: 99%
“…Among various anti-adhesive agents, we have used a poloxamer 407/188-based thermosensitive gel (Mediclore®, CGbio Co., Ltd. Seongnam-si, Korea) [10]. The agent is a complex consisting of poloxamer 407/188, chitosan, and gelatin.…”
Section: Methodsmentioning
confidence: 99%
“…39 Several in vivo studies have shown promising results of TAP hydrogel after spine surgery. 18,19 Poloxamer-based thermo-sensitive agent has shown superior efficacy over hyaluronate-based solution after laminectomy in a rabbit model. 18 However, the present clinical study showed that there was no enhancement of postoperative ROM after TKA in the TAP hydrogel group compared to the control group, consistent with results of a previous study that used conventional (ex-, without poloxamer) anti-adhesive agent periarticularly during TKA.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Poloxamer-based thermo-sensitive agent has shown superior efficacy over hyaluronate-based solution after laminectomy in a rabbit model. 18 However, the present clinical study showed that there was no enhancement of postoperative ROM after TKA in the TAP hydrogel group compared to the control group, consistent with results of a previous study that used conventional (ex-, without poloxamer) anti-adhesive agent periarticularly during TKA. 8 Although TAP hydrogel is a new generation of hydrogel expected to have favorable results, it failed to improve ROM compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other experimental rabbit studies 4,6,19,21 about the degree of peridural adhesion after using Guardix-SG ® have lasted usually 4 to 6 weeks to allow time for dense fibrosis to form at the laminectomy site. In addition, previous studies have reported that significant bone regeneration can be seen about 9 weeks postoperatively in rabbit models 22 .…”
mentioning
confidence: 99%